A design training on packaging and labeling of shredded toman fish and honey in Tahura Lati Petangis, Paser Regency - Ramadhan S. Pernyata; Dita Andansari; Royke Vincentius Febriyana; Rony H. (Universitas Muhammadiyah Magelang, 2021)
This community service aims to improve the quality of Toman Fish Shredded and Honey products that have competitiveness, differentiation and strong and aesthetic packaging through training in design of packaging and label. The community service was held in the Lati Petangis Grand Forest Park (Tahura) area, Paser Regency. The objects of this community service are the Forest Farmers Group (KTH) and the Women Farmers Group (KWT). The problems faced by KTH and KWT are: (1) the flagship product has not been packaged in a good and attractive packaging; and (2) lack of skills in making packaging and label designs. This training requires several graphic design applications, so that KTH and KWT's flagship products have the attractive packaging and labels. The output produced is an increase in skills in packaging design and innovative product labels which are expected to increase sales of superior products.